Whole genome sequence analyses-based assessment of virulence potential and antimicrobial susceptibilities and resistance of Enterococcus faecium strains isolated from commercial swine and cattle probiotic products. (12th February 2022) - Shridhar, Pragathi B; Amachawadi, Raghavendra G; Tokach, Mike; Patel, Isha; Gangiredla, Jayanthi; Mammel, Mark; Nagaraja, T G
Abstract: Enterococcus faecium is one of the more commonly used bacterial species as a probiotic in animals. The organism, a common inhabitant of the gut of animals and humans, is a major nosocomial pathogen responsible for a variety infections in humans and sporadic infections in animals. In swine and cattle, E. faecium- based probiotic products are used for growth promotion and gut functional and health benefits. The objective of this study was to utilize whole genome sequence-based analysis to assess virulence potential, detect antimicrobial resistance genes, and analyze phylogenetic relationships of E. faecium strains from commercial swine and cattle probiotics. Genomic DNA extracted from E. faecium strains, isolated from commercial probiotic products of swine ( n  = 9) and cattle ( n  = 13), were sequenced in an Illumina MiSeq platform and analyzed. Seven of the nine swine strains and seven of the 13 cattle strains were identified as Enterococcus lactis, and not as E. faecium. None of the 22 probiotic strains carried major virulence genes required to initiate infections, but many carried genes involved in adhesion to host cells, which may benefit the probiotic strains to colonize and persist in the gut. Strains also carried genes encoding resistance to a few medically important antibiotics, which included aminoglycosides [ aac(6ʹ)-Ii, aph(3ʹ)-III, ant(6)-Ia ], macrolide, lincosamide and streptogramin B ( msrC ), tetracyclines [ tet (L) and tet (M)], and phenicols [ cat-(pc194) ]. The comparison of the genotypic to phentypic AMR data showed presence of both related and unrelated genes in the probiotic strains. Swine and cattle probiotic E. faecium strains belonged to diverse sequence types. Phylogenetic analysis of the probiotic strains, and strains of human ( n  = 29), swine ( n  = 4), and cattle ( n  = 4) origin, downloaded from GenBank, indicated close clustering of strains belonging to the same species and source, but a few swine and cattle probiotic strains clustered closely with other cattle and human fecal strains. In conclusion, the absence of major virulence genes characteristic of the clinical E. faecium strains suggests that these probiotic strains are unlikely to initiate opportunistic infection. However, the carriage of AMR genes to medically important antibiotics and close clustering of the probiotic strains with other human and cattle fecal strains suggests that probiotic strains may pose risk to serve as a source of transmitting AMR genes to other gut bacteria. Lay Summary: Probiotics, also called direct-fed microbials, are widely used in swine and cattle production systems, as an alternative for antibiotics. The benefits of feeding probiotic products include growth promotion and gut functional benefits. One of the more common bacterial species used in swine and cattle commercial probiotic products is Enterococcus faecium. The species is also a member of the normal flora of hindgut of humans and animals. In recent years, the species has emerged as a major hospital-acquired infection in humans, mainly because of the propensity to become resistant to antibiotics. In the United States, the species is considered as generally recognized as safe. In this study, the virulence and antimicrobial resistance genes profiles of 9 and 13 E. faecium strains isolated from commercial swine and cattle probiotics, respectively, were assessed by sequencing the whole genome DNA. The analysis indicated that 14 of 22 strains were Enterococcus lactis, and not E. faecium. The absence of major virulence genes characteristic of the clinical E. faecium strains suggests that the strains are unlikely to initiate opportunistic infection. However, the carriage of genes that confer resistance to medically important antibiotics suggests that probiotic strains may pose risk as a source of antimicrobial resistance genes to other bacteria. Abstract : Whole genome sequencing of Enterococcus faecium strains isolated from commercial swine and cattle probiotics revealed carriage of genes that confer resistance to medically important antimicrobials.